Sharing a Meme! Questioni di genere tra stereotipi e détournement - Bracciale, Roberta (SocietàMutamentoPolitica, 2020)
Memes are the perfect digital products for virality and therefore visibility in digital spaces. They can no longer be considered only as an expression of frivolous activities on the margins of the political discussion but must be observed as daily practices through which citizens engage in politics and redefine the coordinates of mainstream ideology. These entertaining political-cultural artefacts, which create collective and shared meanings and spread by “leaping from brain to brain”, have produced a process of “memification of the public sphere” that develops along two main attributes: on one hand they offer new opportunities of participation and mobilization, on the other they are soaked in dominant mainstream ideology. This contribution aims to analyze two main aspects: (1) the critical issues deriving from gender stereotyping mechanisms in comparison with the opportunities for polyvocality and widening participation; (2) the reframing and detournement processes, intended as a subversion of stereotypical frames through the fluid language of anti-ideology. The coexistence of these two aspects is addressed and exemplified with reference to a recent case study in Italy.